Unveiling cultural intelligence: A comparative study of Japanese and Indonesian idiomatic expressions - Agus Suherman Suryadimulya; Reiza D. Dienaputra; Awaludin Nugraha; Susi Machdalena; Nyai Kartika (Indonesian Journal of Applied Linguistics, 2023)
This paper delves into the realm of cultural intelligence inherent in Japanese and Indonesian idiomatic expressions. In the context of intercultural communication, Indonesian speakers utilize diverse cultural intelligence frameworks to express various facets of Japanese culture, with language serving as a prominent component. While a plethora of studies have examined idioms from semantic and semiotic perspectives, a notable gap exists in the literature regarding the exploration of cultural intelligence within idiomatic expressions in both languages, encompassing both structural and semantic analyses. Filling this research void, the present study aims to elucidate the concept of cultural intelligence, specifically focusing on the comprehension of Japanese and Indonesian idioms, particularly those related to the notion of "face". Employing a descriptive research approach, data comprising 16 Japanese idioms and 13 Indonesian idioms were meticulously examined to unveil the cultural significance within each group. The idioms were sourced from various dictionaries and specifically focused on expressions related to body parts, especially the face, which are commonly employed in everyday life. These idiomatic expressions were systematically classified into three categories and subjected to comprehensive analysis. The findings reveal that the majority of the idioms convey emotions, personal characteristics, and concepts of honor, thereby reflecting both cultural similarities and differences between Indonesian and Japanese cultures through idiomatic expressions. This study sheds further light on the intersection between cultural intelligence and idiomatic language, enhancing our understanding of how culture influences language use and interpretation.